Multiply. Express your answer as a polynomial in standard form. (1 point)

(3x−5)(9x+1)=
(
3
𝑥

5
)
(
9
𝑥
+
1
)
=

1 answer

To multiply the expressions \( (3x - 5)(9x + 1) \), we can use the distributive property (also known as the FOIL method for binomials).

  1. First: Multiply the first terms: \[ 3x \cdot 9x = 27x^2 \]

  2. Outer: Multiply the outer terms: \[ 3x \cdot 1 = 3x \]

  3. Inner: Multiply the inner terms: \[ -5 \cdot 9x = -45x \]

  4. Last: Multiply the last terms: \[ -5 \cdot 1 = -5 \]

Now, combine all these results: \[ 27x^2 + 3x - 45x - 5 \]

Next, combine like terms: \[ 27x^2 + (3x - 45x) - 5 = 27x^2 - 42x - 5 \]

Thus, the final answer in polynomial standard form is: \[ \boxed{27x^2 - 42x - 5} \]

Similar Questions
    1. answers icon 1 answer
  1. Given: f(x)=2x^2+x-3 and g(x)=x-1Express: f(x)⋅g(x)-[f(x)+g(x)] as a polynomial in standard form
    1. answers icon 1 answer
  2. PLS HELP ME!!I really need the answers to these few questions I need toturn them in ASAP. Simplify each polynomial. Write each
    1. answers icon 2 answers
    1. answers icon 7 answers
more similar questions